Animals' mobilities. (February 2020) - Hodgetts, Timothy; Lorimer, Jamie
This paper draws together animal and mobility studies to develop the concept of animals' mobilities. It identifies the parallel intellectual interests in these fields that provide the intellectual foundations for this synthesis, in mobility (over movement), affect, relational space, and ordering practices. It explores what configures an animal's mobility, knowledge practices for researching and evoking animals' mobilities, and how animals' mobilities are governed. The conclusion highlights what these fields gain from this synthesis, and identifies the empirical, political and conceptual contributions that this concept makes to geographical research. The argument is illustrated with examples of large, terrestrial mammals, especially bears.